Associations of Childhood and Adulthood Cognition with Bone Mineral Density in Later Adulthood: A Population-Based Longitudinal Study - Bendayan, Rebecca; Kuh, Diana; Cooper, Rachel; Muthuri, Stella; Muniz-Terrera, Graciela; Adams, Judith; Ward, Kate; Richards, Marcus (Frontiers in Aging Neuroscience, 2017)
This study explores the association between cognitive ability in childhood and midlife and bone health outcomes in early old age; and the relationships of these bone measures with contemporaneous and subsequent cognitive ability in the MRC National Survey of Health and Development (NSHD). This British birth cohort assessed areal and volumetric bone mineral density (aBMD and vBMD) at age 60-64, derived from peripheral quantitative computed tomography and dual-energy X-ray absorptiometry, and cognitive performance from childhood to age 69, among 866 women and 792 men. Cognitive performance at age 15 was assessed using tests of verbal and non-verbal ability, and mathematics; and memory and search speed tasks were administered at ages 53, 60-64 and 69. Covariates included body size, pubertal timing, smoking, leisure time physical activity, socioeconomic circumstances and menopause timing. Multiple linear regression analyses showed that higher childhood cognitive ability was associated with higher hip aBMD, in women, and greater cortical and trabecular vBMD, in men. For women, there were positive associations between hip aBMD and total vBMD, and contemporaneous cognitive ability with associations also extending to subsequent cognitive ability for total vBMD. For men, some associations with trabecular and total vBMD emerged at ages 60-64 and 69 but only after adjusting for education, occupational class and health behaviours. Our findings highlight that higher cognitive ability in childhood is associated with BMD in early old age and these associations might be explained by social and behavioural pathways. The results suggest that individuals with greater cognitive ability in early life are more likely to engage in healthy behaviours (e.g., leisure time physical activity) in adulthood, which in turn are associated with greater BMD later in life. Associations between bone health and cognitive performance should be considered within a life course framework; and the potential role of smoking and physical activity should be addressed when advising adults at high future risk of osteoporosis and fracture.